Formulasi Gel Ekstrak Daun Kelor (Moringa oleifera Lam.) Sebagai Anti Inflamasi Topikal Pada Tikus (Rattus novergicus) - Maria Ulfa, Wahyu Hendrarti, Prcilya Novelin Muhram (STIFA Makassar, 2016)
The leaves of (Moringa oleifera L) is empirically used in community as an anti-inflammatory. This study aimed to determine the anti-inflammatory effects of ethanolic extract of (Moringa oleifera L) based on the decrease in the volume of the rat foot edema induced by α- carrageenan, inflammation that occurs is measured using a pletysmometer. Tests is performed using Na.CMC as a negative control and Voltaren as a positive control. The results showed that the ethanolic extract (Moringa oleifera L) leaves has anti-inflammatory effects at concentrations of 5% with 47.09% in amount and in stable formulations show the formula 1 with a concentration of 1% carbopol.